Taxonomical considerations of Yucca queretaroensis Piña (Agavaceae), endemic species from the semiarid zone of Queretaro and Hidalgo - Magallán Hernández, Fabiola; Maruri-Aguilar, Beatriz; Sánchez Martínez, Emiliano; Hernández Sandoval, Luis; Luna Zúñiga, Judith (Instituto de Ecología, A.C., 2014)
Yucca queretaroensis is an endemic species of the semiarid zone of Querétaro, Guanajuato and Hidalgo, Mexico. Due to its small population size, restricted distribution and habitat specificity, it is considered rare. This species is listed in the Mexican Official Standard as subject to special protection. When Y. queretaroensis was described as new species, it was placed within series Rupicolae, sectionChaenocarpa. A subsequent treatment placed it in series Gracilifoliae, section Yucca. However, neither of these treatments considered phylogenetic information nor provided a full morphological description of the species. Our goals are to complement the original description of the species including the fruits and seeds; to elaborate a botanical illustration; to compile and discuss the taxonomic history of the species and propose its new taxonomic position, based on morphological and phylogenetic information. We propose to move Y. queretaroensis into series Treculeanae, section Yucca (ex Sarcocarpa) sensuMcKelvey.